Pemanfaatan Media LIPAT (Nilai Tempat) untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Matematika Materi Bilangan Cacah Besar Kelas 5 SD Negeri Pedurungan Lor 01 - Siti Masithoh; Sugiyanti Sugiyanti; Sukamto Sukamto; Ita Laila Puji R (Departement of Mathematics Education, 2024)
This research aims to gain an understanding of: 1) The use of Lipat (Nilai Tempat) media can improve learning outcomes in large whole number material in class V students at SD Negeri Pedurungan Lor 01, 2) The process of learning large whole numbers using Lipat (Nilai Tempat) media in class V students of Pedurungan Lor 01 State Elementary School, and 3) the results of learning large whole numbers using Lipat (Nilai Tempat) media in class V students of Pedurungan Lor 01 State Elementary School. This classroom action research was carried out at Pedurungan Lor 01 State Elementary School, specifically for class V students for the 2023-2024 academic year. The subjects in this research included: 1) all 28 students in class V for the 2023-2024 academic year, consisting of 15 men and 13 women; 2) a teacher, namely the researcher himself; and 3) an observer. Data collection techniques applied in this research include observation, tests and documentation. Based on the research results, it can be concluded that student learning outcomes regarding large whole number material in cycle I are classified as good with an average score of 73.92. Of the 28 students, only 15 people (53.57%) achieved completeness individually. In cycle II, student learning outcomes showed good improvement with an average score of 83.92, where 24 students (85.71%) achieved completeness individually. Thus, the use of Lipat (Nilai Tempat) media has been proven to improve learning outcomes for integer arithmetic operations in class V students at Pedurungan Lor 01 State Elementary School.